"Keeping Us in Our Place": Low-Income Moms Barred From College Success. (February 2019) - Dodson, Lisa; Deprez, Luisa S.
Mothers, trying to graduate their way out of poverty, describe controlling state policies and university cultures of exclusion that seem aligned in barring them from social mobility.